Cameroon Economic Update, January 2011, Issue No. 1 : Time for the Lion to Wake Up? - World Bank (Washington, DC, 2017)
This Cameroon economic update, the World Bank is launching a program of short, crisp and more frequent country economic reports. These economic updates will analyze the trends and constraints in Cameroon's economic development. Each issue, produced bi-annually, will provide an update of recent economic developments as well as a special focus on a selected topical issue. The economic updates aim to share knowledge and stimulate debate among those interested in improving the economic management of Cameroon and unleashing its enormous potential. The notes thereby offer another voice on economic issues in Cameroon, and an additional platform for engagement, learning and change. The report's special focus on the telecommunication sector. Cameroon has been hit by the global economic and financial crisis over the past two years, as reflected in steep declines in the price and demand for its export commodities including oil, timber, rubber, cotton and aluminum. However, the upturn in the global economy and measures taken by the authorities to stimulate domestic production, preliminary indications suggest that economic activity is recovering. Gross domestic product (GDP) growth in 2010 is estimated to have reached 3 percent on the back of stronger non-oil activities, which expanded by about 4 percent (particularly food crops, forestry, construction, transport, and telecoms). Data on private credit growth corroborate this assessment. Cameroon is a relatively small and mature oil producer, where oil production is declining. Depleting reserves, aging equipment, and more recently postponements of some development projects and investments because of the financial crisis explain this profile. The contribution of this sector to GDP growth has been mostly negative in recent years: oil production is estimated to have contracted by a further 16 percent in 2010 (to 23.2 million barrels).